Settlement of the classification of Svistella Gorochov and Paratrigonidium Brunner von Wattenwyl using morphology and molecular techniques, with the description of a new species from Yunnan, China (Orthoptera: Trigonidiidae: Trigonidiinae) - Lu, Hui; Wang, Hang-Qiang; Li, Kai; Liu, Xian-Wei; He, Zhu-Qing (Zootaxa, 2018)
It is difficult to distinguish the genera Svistella and Paratrigonidium on the basis of morphology. Gorochov postulated that Svistella spp. possess the following identification characters: posterior lateral lobes of epiphallus long and narrow at apex, guide rod elongate, attachment plate of the spermatophore consisting of three sclerites (a narrow middle sclerite bearing no protruding structure, and a pair of lateral ones extending to the sides). These features have not been extensively evaluated. In this study, the COI gene was sequenced and was used as a DNA marker to distinguish two genera. The results showed that each genus formed a monophyly, respectively. One new species, Svistella fuscoterminata sp. nov., was found in Yunnan, China. Although its genitalia were similar to that of Paratrigonidium spp., the molecular result supported the new species belonging to Svistella. The specimens are deposited in East China Normal University, Biology of History Museum (ECNU) and Shanghai Entomological Museum (SEM).